Technologies for increasing carbon storage in soil to mitigate climate change. (23rd April 2014) - Whitmore, A. P.; Kirk, G. J. D.; Rawlins, B. G.
Abstract: Means to enhance storage of carbon in soil or avoid its loss from soil are discussed and examined from the viewpoint of policy. In particular, technologies that have until now received little attention are assessed. The main means by which soil carbon might be increased are first listed. These are the following: (i) increasing the rate of input of organic matter; (ii) decreasing the rate of its decomposition by biological or chemical means; (iii) increasing the rate of its stabilization by physico‐chemical protection within aggregates and organo‐mineral complexes; and (iv) increasing the depth or more correctly the total soil volume sequestering carbon at maximum rate. Immediate gains in carbon storage might be made by switching to more perennial crops, especially grasses that, as a result of breeding, are able to put more carbon into soil. In the longer term, targets for research such as understanding the role of enzymes in carbon turnover and the exploitation of the capacity in subsoils are suggested. Increased fixation of CO2 as inorganic carbonate in soils by application of silicate wastes may have some role.